An Approximate Nonlinear Analysis Of Vertically Loaded Piled Rafts In Layered Soils - Seung-hoon Lee (Deep Foundations Institute, 2008)
The use of piled raft foundations has been considered as an economical alternative to conventional piled foundations because a portion of the applied load is carried by the raft in the design of piled raft foundation. In analyzing the behavior of a piled raft foundation as a settlement reducer, an accurate estimate of settlements of the system should be made on the basis of the understanding of nonlinear behavior of piles in layered soils as well as the interaction between the raft, soils, and piles. Although the 3-dimensional finite element method and simplified analysis methods have been used for the design of piled raft foundations, these methods were found to be inadequate for the practical purpose or could not consider the interactions properly. This study developed an approximate hybrid method of analysis to be used for the practical design of piled raft foundations considering pile-soil, raft-soil, pile-soil-pile and raft-soil-pile interactions. In the presented method of analysis, the settlements of the system are estimated satisfying the compatibility of two separate models which are the flexible raft model consisting of 2-dimensional finite elements supported by springs representing soils and piles, and the group-pile model embedded in layers of soil having different properties. Comparisons with other analytical methods as well as a 3-dimensional FEM program were made to verify the sufficient capabilities of the proposed hybrid model for application to practical design and analysis of piled raft foundations.